Frequency of Thyrotoxicosis in Patients Presenting with Unilateral Proptosis in District Headquarters Teaching Hospital D.I.Khan: Thyrotoxicosis with Unilateral Proptosis in Patients - Khan, Salman; Rehman, Naseeb ur; Rehman, Abdur; Zubair, Muhammad; Naz, Rida (Pakistan Journal of Health Sciences, 2024)
Thyrotoxicosis is a medical disorder marked by retraction of the eyelids, resulting in a wide-eyed or gazing appearance. This syndrome can occur in patients with any form of hyperthyroidism as a result of increased activity of the sympathetic nervous system. Objectives: To investigate the prevalence of thyrotoxicosis and factors contributing to unilateral proptosis, with a specific focus on early diagnosis and prompt treatment. Methods: A cross-sectional study was conducted from January 2023 to January 2024 and categorical variables were presented with the frequency and percentage. The study had a total of 62 patients who exhibited unilateral proptosis. The clinical examinations involved a comprehensive collection of medical history, examination of eyes, analysis of blood samples, evaluation of thyroid function, and utilization of advanced imaging techniques. The associations between thyrotoxicosis and demographic variables were evaluated using chi-square tests. Data were entered and analyzed on SPSS version 26. Results: The mean age of participants was 27.84 ± 6.8 years and female comprised 54.8% of the total. It was observed that female had a greater incidence rate (73.5%) compared to male (53.6%) (p>0.05). Additional findings included retrobulbar tumors (16.1%), cavernous sinus thrombosis (12.9%), and idiopathic proptosis (6.5%). The prevalence of thyrotoxicosis was highest among individuals aged 15-30 (p<0.05). The most common symptom linked with thyrotoxicosis was diplopia (33.9%) (p<0.05). Conclusions: Thyrotoxicosis has a major role in causing unilateral proptosis, especially in female and younger persons. Being female and experiencing pain may serve as predictors for thyrotoxicosis.